THE MISSILE GUIDANCE ESTIMATION USING EXTENDED KALMAN FILTER-UNKNOWN INPUT-WITHOUT DIRECT FEEDTHROUGH (EKF-UI-WDF) METHOD - Subchan, Subchan; Asfihani, Tahiyatul (Journal of the Indonesian Mathematical Society, 2013)
This paper consider the estimation of the optimal missile guidance which the objective is to minimize the interception time and the energy expen-diture. The proposed Extended Kalman Filter-Unknown Input-Without Direct Feedthrough (EKF-UI-WDF) approach is to estimate the optimal missile guidance and the target acceleration as unknown input to the missile-target interception model. Unknown input is any type of signals without prior information from agiven state model or a measurement. The computational for the EKF-UI-WDF method and optimal missile guidance show the closest range to the missile-target is smaller than using the EKF. However the Mean Squared Error (MSE) of estimating the optimal missile guidance using EKF method is smaller than using EKF-UI-WDF method.DOI :Â http://dx.doi.org/10.22342/jims.19.1.124.1-14